Evangelizar ou humanizar? - Miranda, Mário de França (Revista Eclesiástica Brasileira, 2014)
O artigo aborda o desafio de uma linguagem evangelizadora numa sociedade complexa e pluralista. Na primeira parte, descrevemos as mudanças socioculturais que experimentamos e a possibilidade de uma modalidade de anúncio que seja universal e atinja a todos. Na segunda parte, oferecemos os pressupostos teológicos para esta modalidade: Jesus e o Reino de Deus, a distinção entre fé e religião e, ainda, a dimensão simbólica do cristianismo. Na terceira e última parte, abordamos o “humano cristão” como resposta pastoral aos desafios de hoje e, consequentemente, à missão atual do cristianismo, bem como às mudanças exigidas tanto de mentalidade quanto de estruturas. Abstract: This article addresses the challenge of finding an evangelizing language in a complex and pluralistic society. In the first part, we describe the sociocultural changes we have experienced and the possibility of a form of communication that is universal and reaches everyone. In the second part, we offer the theological presuppositions for this modality: Jesus and the Kingdom of God, the distinction between faith and religion and also the symbolic dimension of Christianity. In the third and final part, we discuss the “Christian human” as a pastoral response to the challenges of today and hence to the current mission of Christianity, as well as to the changes required both in mentality and in structures. Keywords: Evangelization. Kingdom of God. Christian faith. Christian human. Pastoral conversion.